The number of endemic species of freshwater sponges (Malawispongiidae; Spongillina; Porifera) from Lake Kinneret is overestimated. (29th May 2013) - Itskovich, Valeria; Kaluzhnaya, Oxana; Ostrovsky, Ilia; McCormack, Grace
Abstract It is well accepted that the freshwater sponges (Porifera; Haplosclerida; Spongillina) currently comprise six extant families: Spongillidae, Lubomirskiidae, Malawispongiidae, Metaniidae, Metschnikowiidae and Potamolepidae, but the phylogeny of this group is poorly understood. Family Malawispongiidae includes five genera: Malawispongia, Spinospongilla, Cortispongilla, Ochridaspongia, Pachydictyum, which inhabit ancient lakes: Malawi and Tanganyika (African Rift Valley), Kinneret (Middle East), Ohrid (Europe) and Poso (Central Sulawesi). We show via nuclear and mitochondrial markers (cox 1, 28S rRNA and ribosomal ITS regions) that both endemic species Cortispongilla barroisi and Ephydatia syriaca from Lake Kinneret are synonymous with the cosmopolitian species Ephydatia fluviatilis, which also supports suggestions that the family Malawispongiidae is polyphyletic. Our findings also suggest that Nudospongilla is a synthetic taxon and that the number of endemic freshwater sponge species is overestimated.